Posterior Corneal Asphericity and the Refractive Outcome after Combined Phacovitrectomy - Rabinovich, Mark; Baumgartner, Jean-Marc; Bovet, Jerome (Klinische Monatsblätter für Augenheilkunde, 2023)
Background We assessed the correlation of posterior corneal asphericity and the refractive prediction error of the SRK-T and Barrett II Universal formulas for eyes following phacovitrectomy with peeling of the internal limiting membrane (ILM).Patients and Methods We retrospectively analyzed 41 eyes of 41 patients following a combined phacovitrectomy with ILM peeling. Surgeries were performed by one fellowship-trained vitreoretinal surgeon between 2016 and 2021.Results Of the 41 patients, 41 eyes were included, with all having at least 1 month of postoperative data. Of the 41 eyes, 19 eyes were female (46%) and 22 were male (54%). The average age of the study population was 77.5 ± 10.7 years. The mean axial length (AL) was 22.7 ± 4.6 mm and the mean anterior chamber depth (ACD) was 3 ± 0.8 mm. The mean posterior Q value was − 0.29 ± 0.27. The mean absolute error (MAE) values 1-month postoperatively for the SRK-T and Barrett II Universal formulas were 0.73 and 0.65, respectively. Regression analysis yielded a significant correlation between posterior corneal asphericity and SRK-T MAE (r = 0.35, R2 = 0.12, p < 0.05) only.Conclusions Posterior corneal surface asphericity is correlated to the refractive error of the SRK-T formula for eyes following phacovitrectomy.
Keywords: asphericity; phacovitrectomy; cataract; internal limiting membrane